Terror/enjoyment: performativity, resistance and the teacher's psyche (UCL Press, 2013)
This paper focuses on Stephen Ball's article, The teacher's soul and the terrors of performativity, since it is here that he analyses the issue of how neoliberal education policies shape teacher identities that I also wish to explore. I begin by providing a summary of the 2003 piece, noting how it locates teachers and their work in the midst of policy, politics, and passion in contrast to dominant techno-rational discourses of teaching - embodied, for example, in discourses of professional teacher 'standards' or 'competencies' that reduce teaching to matters of technical efficiency. As part of this summary, and complementing Ball's own use of Foucault, I use the four 'axes' of Foucault's ethics to explain how performativity has brought about changes in relation to (1) the domain, (2) the authority sources/mode of subjectivization, (3) the practices and (4) the telos of being a teacher. The paper goes on to argue that Ball's emphasis on 'terror' can usefully be supplemented by a Lacanian-inspired recognition of 'enjoyment' as an explanatory factor that help us understand the grip of neoliberalism's ideology of performativity. The paper concludes by examining the economies of fantasy and enjoyment as they relate to the work of teachers, how these economies work to sustain the terrors of performativity, and how an ethics of the Real that emphasizes the critical and creative potential of sublimation, might form part of a repertoire of resistance.